Implementation Of Live Digital Marketing Communication Style Streaming - Amalia, Nadia; Firliandoko, Robby; Wahyudin, Cecep; Sukarelawati, Sukarelawati (JURNAL KOMUNIKATIO, 2024)
Communication is an important aspect in carrying out daily activities, the development of communication in the era of the 21st century has seen rapid development, a rapid development revolution in digital. This development was followed by the rapid growth of internet users, as seen by the number of internet users increasing rapidly Total Population (population): 7.83 billion Unique Mobile Users: 5.22 billion (66.6% of the world's population), Internet Users: 4 .66 billion (59.5% of the world's population), Active Social Media Users: 4.20 billion (53.6% of the world's population). With the background of conflict between online and direct traders, researchers were interested in taking the title Digital Marketing Communication Style. From this number, the researcher took the aim of finding out effective communication styles. This research uses qualitative data by analyzing samples. The aim of this research is to find out the model.